Pemberdayaan Masyarakat Dalam Pengembangan Desa Wisata, Studi Kasus : Desa Wisata Pentingsari, DIY - Raden Harya Andrianto; Maya Damayanti (Teknik PWK (Perencanaan Wilayah Kota), 2018)
Tourist village is one of the alternative approaches of sustainable tourism development. One of the goals of this tourism village is to develop the natural potential in an area or village while maintaining local culture as a tourist attraction. Furthermore, to realize a good tourist village, intervention and direct involvement are needed in the management of tourist village. This can be done by conducting community empowerment activities in economic, social, and environmental aspects. Pentingsari Tourist Village is one of the tourist villages that developed quite well and managed to apply the principle of community empowerment in its development. This can be seen when Pentingsari Tourist Village won the second place in Sleman Regency Tourist Village Competition in 2008 and the first winner of DIY Tourist Village Competition in 2009. This research used a descriptive qualitative method with the aim to see how the community empowerment process in Pentingsari Tourist Village.Community empowerment in Pentingsari Tourist Village beganwith the previous process of tourist village formation to Pentingsari Tourist Village at this time. Various forms of training have been given to the community as an effort to empower the community. This assistance is carried out by various parties, including the government, namely the Tourism Office of Sleman Regency, as well as the private sector. One of them is training from PT. Bank Central Asia (BCA).Tbk, which provides training to the public in the form of excellent service standards. These things show that the empowerment process carried out in the Pentingsari Tourist Village was going gradually. This is also influenced by several supporting factors, such as the driving actors, the community, the role of the government, and the private sector.